2007
DOI: 10.1007/s11906-007-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

The NTS and integration of cardiovascular control during exercise in normotensive and hypertensive individuals

Abstract: Due to upward resetting of baroreceptors, tachycardia coexists with increased pressure during dynamic exercise. This review critically evaluates current knowledge of proposed mechanisms to explain the continuous resetting of baroreflex control of heart rate and sympathetic nerve activity during and after exercise and exercise training. Of interest is the exercise-induced upward resetting that occurs in hypertensive and normotensive individuals. Accumulated evidence indicates that not only somatosensory afferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 52 publications
2
41
0
8
Order By: Relevance
“…These changes significantly correlated with training-induced reductions in resting HR. A long cascade of events elicits these effects, triggered by an increase in pressure during repetitive exercise: 1) increased afferent signaling to the NTS (7), 2) increased noradrenergic drive from NTS to PVN preautonomic neurons (18), 3) structural remodeling of trained PVN preautonomic neurons that exhibit stronger dendritic branching and a larger surface area compared with sedentary controls (29), 4) increased OT mRNA expression in the PVN and substantial augmentation of peptide density within parvocellular PVN OTergic neurons (present data in trained intact controls), 5) increased intrinsic excitability, specifically in PVN-NTS-projecting neurons, with diminished input-output function in PVN magnocellular neurons that project to the neurohypophysis (20), 6) augmented OTergic projections from the PVN to the NTS/DMV complex in trained individuals (23,26), 7) facilitated vagal outflow to the heart during OTergic stimulation (16,27), and 8) resting bradycardia in both trained WKY and SHR rats, which correlated with peptide content within OTergic preautonomic neurons (present study).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These changes significantly correlated with training-induced reductions in resting HR. A long cascade of events elicits these effects, triggered by an increase in pressure during repetitive exercise: 1) increased afferent signaling to the NTS (7), 2) increased noradrenergic drive from NTS to PVN preautonomic neurons (18), 3) structural remodeling of trained PVN preautonomic neurons that exhibit stronger dendritic branching and a larger surface area compared with sedentary controls (29), 4) increased OT mRNA expression in the PVN and substantial augmentation of peptide density within parvocellular PVN OTergic neurons (present data in trained intact controls), 5) increased intrinsic excitability, specifically in PVN-NTS-projecting neurons, with diminished input-output function in PVN magnocellular neurons that project to the neurohypophysis (20), 6) augmented OTergic projections from the PVN to the NTS/DMV complex in trained individuals (23,26), 7) facilitated vagal outflow to the heart during OTergic stimulation (16,27), and 8) resting bradycardia in both trained WKY and SHR rats, which correlated with peptide content within OTergic preautonomic neurons (present study).…”
Section: Discussionmentioning
confidence: 83%
“…A series of studies indicated that low-intensity aerobic training in normotensive Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats improved afferent signaling by aortic baroreceptors (7) and increased noradrenergic drive from the brain stem to hypothalamic preautonomic neurons (18). Training also caused structural remodeling and increased the intrinsic excitability of oxytocinergic (OTergic) and vasopressinergic (VPergic) neurons within the paraventricular nucleus (PVN) of the hypothalamus that project to the brain stem (20,29), thus activating OTergic and VPergic drive to dorsal brain stem areas (23,26,29). Oxytocinergic input is involved in the modulation of vagal outflow to the heart, causing resting bradycardia and smaller exercise tachycardia in trained WKY and SHR rats (6,16,17,25).…”
mentioning
confidence: 99%
“…of ascending/descending pathways that integrate bulbar and hypothalamic areas involved in cardiovascular control. For a comprehensive understanding of the central effects on autonomic pathways in both normotensive and hypertensive individuals the reader is referred to other excellent papers and reviews (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The functional consequences of these distinct stage-dependent responses need to be interpreted through the location and role of these brain-stem nuclei in the blood pressure control circuit. The NTS is known to be the primary site of cardiorespiratory regulatory integration (1,8,9,13,33,46,47). The RVLM receives inhibitory projections from the caudal ventrolateral medulla.…”
Section: Discussionmentioning
confidence: 99%